Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

urgent

Asked by 2806rahul 16th May 2010, 8:50 PM
Answered by Expert
Answer:

cot θ - cot3θ = 1/tan θ - 1/tan3θ = (tan3θ - tanθ)/tanθ tan3θ       .......(1)

Now,

[cot θ/(cot θ - cot3θ)] + [tan θ/(tan θ - tan3θ)] =

Using (1) to replace the denominator in first term,

[tanθ tan3θcot θ/((tan3θ - tanθ)] + [tan θ/(tan θ - tan3θ)] =

[tan3θ/((tan3θ - tanθ)] + [tan θ/(tan θ - tan3θ)] =                         ... tanθ cotθ = 1

[- tan3θ/((tanθ - tan3θ)] + [tan θ/(tan θ - tan3θ)] =

(tan θ - tan3θ)/(tan θ - tan3θ) = 1

Regards,

Team,

TopperLearning.

Answered by Expert 17th May 2010, 7:11 AM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp